Non-physiological rate response in the pacemaker using activity sensor: assessment by rate profile and redraw function - YAMAMOTO Y (Jinko Zoki, 1995)
Non-physiological rate response in the pacemaker using activity sensor assessment by rate profile and redraw function. Rate response in the pacemaker using activity sensor is not uniform in the daily activities. We studied the effects of slope, jogging, stairs on rate response quality of SSIR pacemaker DASH (Intermedics Ltd), using internal rate profile and redraw functions. Exercise tests were performed by three protocols. Protocol (1) includes walk on treadmill with slope of 0% and 14% at 2.0mph and 3.4mph for 3min at each stage of exercise. Protocol (2) includes walk on treadmill with 0% slope at 2.0mph, 3.4mph, 4.2mph and jog at 4.2mph. Protocol (3) includes walk and Master two steps tests with constant speed of 100 steps/min. Sinus rate and activity sensor rate profiles of different settings of rate response parameters were compared. As the result, if rate response parameters were set optimal to walk speed, sensor rate was under-responsive both to slope and stairs, and over responsive to jogging. Thus, one setting of rate response parameters was not optimal to all of daily activities. This is a limitation of rate response quality by activity sensor. 坂道歩行、階段歩行、駆け足に対する体動センサーによるレート応答特性を明らかにすることを目的に、ペースメーカー内蔵rate profile機能およびredraw機能を用い、実験を行なった。健常男子1名を対象に、Intermedics社製DASHを胸壁に絆創膏固定し、(1) 歩行速度2.0mph、3.4mph、傾斜度0%、14%を組合せた各段階3分間のプロトコール、(2) 歩行速度2.0mph、3.4mph、4.2mph、駆け足4.2mphの各段階3分間のプロトコール、(3) 歩数100歩/分での平地歩行、Master 2階段試験各3分間のプロトコールに従い運動負荷試験を実施した。その結果、歩行速度に対する洞調律の増加に対応するようなパラメーター設定では、傾斜度の増加、階段に対しては過小応答、駆け足に対しては過剰応答を示した。以上の結果から、体動センサーの場合、同一のレート応答パラメーター設定では、異なった運動全てに対し生理的に対応することは困難であると考えられた。